‘Recorded by the School of Scottish Studies…’ The Impact of the Tape-Recorder In a Rural Community - Bennett, Margaret (Scottish Studies, 2017)
‘Recorded by the School of Scottish Studies…’ The Impact of the Tape-Recorder In a Rural Community  Most people in Scotland interested in traditional songs and stories will have heard the phrase ‘they were recorded by the School of Scottish Studies’. From 1951, when the School was founded, those whose songs, stories and oral traditions were of interest to collectors and research staff enjoyed the prestige of having their names linked with what has become our national collection. For many years, the fact that a singer or story-teller had been ‘recorded by the School of Scottish Studies’ would often form part of an introduction at a ceilidh or a concert.